Advanced Computational Materials Modeling: From Classical to Multi-Scale Techniques - Vaz Jr. M.* (2010)
With its discussion of strategies for modeling complex materials using new numerical techniques, mainly those based on the finite element method, this monograph covers a range of topics including computational plasticity, multi-scale formulations, optimization and parameter identification, damage mechanics and nonlinear finite elements. © 2011 Wileyâ-VCH Verlag GmbH & Co. KGaA.